Environmental Gradients and Spatial Patterns of Calanoid Copepods in the Southeast Pacific - González, Carolina E.; Medellín-Mora, Johanna; Escribano, Rubén (Frontiers in Ecology and Evolution, 2020)
Understanding the mechanisms maintaining the biodiversity of plankton communities in marine ecosystems subject to a strongly variable ocean has become a critical issue for modern oceanography. Here, we used data on distribution of calanoid copepods in the upper layer of the ocean (0-500 m), a widely distributed taxonomic group in the pelagic realm, to assess the effects of changing oceanographic conditions on their diversity patterns and family and species richness. Copepods abundance and occurrence were evaluated from 2002 to 2015 covering the region extended between the coastal upwelling zone and the offshore region of Chile at subtropical and temperate areas. We used spatial analyses of community structure descriptors, such as abundance and diversity (family and species richness), multivariate analysis and General Additive Models (GAMS) in order to study the effect of surface temperature and its gradients, mixed layer depth, salinity and Chlorophyll-a on copepod diversity. 17 families were identified comprising 151 species distributed in 3 predefined zones in the onshore-offshore gradient covering the coastal upwelling, the coastal transition and the oligotrophic zones, whereas over the alongshore gradient, same families were majorly linked to the northern and southern portions of the sampled area (20°S to 40°S). Families and species were significantly structured over the zonal gradient, revealing the dominant habitat for each of the families. Spatial patterns revealed the presence of transitional zones comprised by mixed taxa. Over the alongshore gradient this transition zone was linked to the subtropical convergence (30°S). The spatial variation of sea surface temperature (SST) revealed strong environmental zonation of temperature gradients across onshore-offshore and alongshore dimensions. Mean SST combined with mean mixed layer depth explained about 40% and about 29% of variation in family and species richness, respectively over the onshore-offshore axis. We thus conclude that the environmental zonation imposed by SST and its spatial gradients, considered as ecological barriers, is the key driver for maintaining diversity of copepods in the southeast Pacific.